Integration of innovation through analytical hierarchy process (AHP) in project management and planning - Gunduz, Murat; Alfar, Mohammed (Technological and Economic Development of Economy, 2019)
This paper examines the concept of innovation management in the construction industry by studying the major components of the innovation process such as the major drivers of innovation, barriers and obstacles that prevent innovation, the enablers that motivate innovation, the practices of innovation, and the benefits of innovation both at project and company level. This paper is based on the data collected by means of structured questionnaires and analyzed throughsurvey analysis. The survey, which consisted of 46 factors involved in the innovation process, was distributed to 121 different participants, and the collected data were analyzed by the relative importance index (RII), as well as the analytical hierarchy process (AHP). The RII rankings feed the AHP analysis as the first step to rank the factors. Later, the factors are ranked according to the AHP analysis. Based on these rankings, recommendations are made to contractors, consultants, project management professionals, owners and suppliers.